Professor Jørgen Vestbo: advances on the management of COPD - He, Chao-Xiu (Melanie) (Journal of Thoracic Disease, 2015)
Professor Jørgen Vestbo (Figure 1) is a Professor of Respiratory Medicine at the University of Manchester and an Honorary Consultant at the North West Lung Centre, University Hospital South Manchester NHS Foundation Trust. His professional training consisted of specialist training in Internal Medicine and Respiratory Medicine in university hospitals in Copenhagen. He obtained a DrMedSci degree from the University of Copenhagen in 1992.